Mood Disorders Induced by Maternal Overnutrition: The Role of the Gut-Brain Axis on the Development of Depression and Anxiety - Jantsch, Jeferson; Tassinari, Isadora D’Ávila; Giovenardi, Márcia; Bambini-Junior, Victorio; Guedes, Renata Padilha; de Fraga, Luciano Stürmer (Frontiers in Cell and Developmental Biology, 2022)
Since the first evidence suggesting that maternal nutrition can impact the development of diseases in the offspring, much has been elucidated about its effects on the offspring's nervous system. Animal studies demonstrated that maternal obesity can predispose the offspring to greater chances of metabolic and neurodevelopmental diseases. However, the mechanisms underlying these responses are not well established. In recent years, the role of the gut-brain axis in the development of anxiety and depression in people with obesity has emerged. Studies investigating changes in the maternal microbiota during pregnancy and also in the offspring demonstrate that conditions such as maternal obesity can modulate the microbiota, leading to long-term outcomes in the offspring. Considering that maternal obesity has also been linked to the development of psychiatric conditions (anxiety and depression), the gut-brain axis is a promising target to be further explored in these neuropsychiatric contexts. In the present study, we review the relationship between maternal obesity and anxious and depressive features, exploring the gut-brain axis as a potential mechanism underlying this relationship.